A Study on the Contribution of Knowledge Identification to Knowledge Management Effectiveness - Newk-Fon Hey Tow, William Foong Kim (Curtin University, 2017)
Many organisations have blind spots; they often do not know what they know already. This research investigates how organisations establish what knowledge they have and to what extent this process of identifying relevant and needed knowledge that exists within organisational boundaries (a process referred to as Knowledge Identification or KI) contributes to effective Knowledge Management (KM). Following a three-phased, mixed-method research design, results confirmed the critical nature of the relationship between KI and KM.